Die Großschmetterlinge (Macrolepidoptera) der Diluviallandschaften um Eberswalde. Vierter Nachtrag, Ergänzungen zur Verbreitung, Biologie und Phänologie seit 2013 - Richert, Arnold (Contributions to Entomology = Beiträge zur Entomologie, 2018)
The changes in the fauna of macrolepidoptera of the diluvial landscapes around Eberswalde was described until the year 2018 considering the following major aspects: (1) Changes in species composition: Four species were newly recorded; eight species thought to have disappeared were rediscovered, with two particularly remarkable findings, the Nolidae Eremobia ochroleuca after >60 years of absence and the Geometridae Eustroma reticulata after 33 years; eight of the species known for the region could not be confirmed by newer records. (2) Additions are given to the knowledge of the biology, especially of the nutrition ecology of butterflies, as well as recent changes in the phylogeny. (3) Examination of older sources, which have not been known by the author before; these allowed completing the overall picture of the macrolepidoptera. (4) Supplementary information on the level of knowledge on the different sub-regions is given.
Keywords: butterflies; moths; phenology; ecology; time series; long-term research; species composition; nature conservation; Brandenburg